Work : A Very Short Introduction - Fineman, Stephen (Oxford Oxford University Press, 2012)
Work is deeply embedded in the moral and political character of most societies. For many, work becomes fused with our personal and social identities - who we are and how we define ourselves. Steve Fineman explores the key debates about work and the factors that affect it including topics such as globalization, feminism, and technology.
Include Illustrations, References and Index.
A Very Short Introduction.
Keywords: Work -- Work - Psychological aspects -- Work - Social aspects